Hak Masyarakat Untuk Menyuarakan Pemikirannya Di Media Sosial (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
This article explores people's right to voice their thoughts on social media and the related legal implications. Freedom of speech and expression is a fundamental right recognized in many constitutions and human rights laws around the world. In the digital era, social media has become the primary platform where individuals can voice opinions, share information, and engage in public discussions. This article reviews important aspects, such as the legal framework that protects the right to free speech on social media, the limitations that can be imposed by law, and issues related to privacy, insults, or the spread of false information. Additionally, this article also considers the role of social media companies in managing content and the right to enforce their community guidelines. During the exploration, this article provides a comparison of laws and regulations in various countries, as well as changes in practices and policies on social media that influence the way people voice their thoughts. In addition, this article highlights the important role of people's right to voice their thoughts in shaping public opinion, contributing to social issues, and strengthening democracy.